The wildest sun : a novel - Lemmie, Asha (Dutton, 2023)
Forced from her home in postwar Paris, aspiring young writer Delphine Auber embarks on a journey to New York's Harlem, and then to Havana and Key West, in search of her father, whom she believes is famed luminary Ernest Hemingway.